STUDENTS’ PERCEPTION TOWARDS THE USE OF JOOX APPLICATION TO IMPROVE STUDENTS’ PRONUNCIATION - Anggun Hervi Rahmania; Berlinda Mandasari (fsip.teknokrat.ac.id, 2021)
Student in Indonesia has many regional accents. It influences them when they are pronouncing English words. Most of them thought that pronunciation is quite-hard. However, with the use of application media could help students in the learning process. One of the applications that can be used as a medium to improve the student pronunciation is JOOX. In this paper, the researcher will investigate student’s perception towards the use of JOOX Application to improve their pronunciation. Furthermore, the researcher uses descriptive qualitative as a method of the study. The participants of the study are 20 students of English Education batch 17 at Universitas Teknokrat Indonesia. Data were collected through questionnaire and interview. After collecting the data, the researcher analyzes the data by tabulating data. The result revealed that most of the students (74%) are agreed that JOOX application help them to get better pronunciation with the help of lyrics features in JOOX application.